Making CGIAR outputs open and accessible: The CGSpace collaboration - Yabowork, Abenet; Orth, Alan S.; Ballantyne, Peter G. (2017)
In recent years, CGIAR centres and research programs have moved towards open access as part of commitments to make CGIAR information products widely accessible. These efforts span a wide variety of activities including adoption of policies, awareness raising, using open licenses and establishing ope n access repositories for products as well as data. This article explains the origins, operation and uses of the CGSpace repository set up in 2009 by the International Livestock Research Institute with several partners. Starting from an “institutional” effort, it has evolved into a collaboration among dozens of programs and entities, pooling technical efforts and generating collective public goods for the wider agricultural world. This article covers the CGSpace and open access value proposition, technical developments and choices, content management and standards, use and update, metrics and reach, as well as lessons and promising practices for wider use.